Structural, Morphological, and Optical Properties of Zn-Doped Cu2O for the Removal of Dyes and Antibiotics from Aqueous Media - Van Thanh, Hoang; Quan, Nguyen Doan Tung; Minh, Dinh Thi Ngoc; Cham, Le Thi Minh; Co, Nguyen Dang; Thien, Trinh Duc; Tuan, Mai Van; Lam, Nguyen Dinh (Communications in Physics, 2026)
This study focuses on the synthesis and characterization of zinc (Zn)-doped cuprous oxide nanoparticles, denoted as ZnxCu2O, prepared by a room-temperature co-precipitation method. The Zn doping content was varied from 0 to 30%. X-ray diffraction (XRD) confirmed that the nanoparticles predominantly exhibit the cubic Cu2O phase. With increasing Zn content, the crystallite size gradually decreased, consistent with changes in lattice parameters and microstrain. Raman and FTIR analyses verified successful Zn incorporation, revealing modifications in Cu-O vibrational modes and the emergence of Zn-O bonding features. FE-SEM observations showed reduced particle size and increased agglomeration at higher Zn doping levels, in agreement with XRD results. Optically, the band gap energy (Eg) increased at low Zn doping due to the Burstein–Moss effect, then decreased at higher doping levels because of secondary ZnO phase formation. Photocatalytic experiments demonstrated that the sample with an optimal Zn content of 10% (x = 0.1) exhibited superior degradation performance toward common organic pollutants, including Rhodamine B, ciprofloxacin, and sulfamethoxazole. These results highlight the strong potential of ZnxCu2O nanomaterials for wastewater treatment and environmental remediation.